Effect of storm separation time on rainfall characteristic - a case study of Johor Malaysia - Shamsudin, Supiah; Dan'azumi, Salisu; Aris, Azmi (EuroJournals Publishing, Inc., 2010)
Planning and design of agricultural, runoff and pollution control systems demand input of rainfall data, mostly, at sub-daily scale. Therefore, the need to explore rainfall characteristics at fine scale becomes important. It is known that, using the same data, the rainfall characteristics may differ depending on the minimum inter-event time definition (MIT) used. Moreover, there is the problem of chosen a criteria for separating the rainfall events as the definition of the MIT separating two rainfall events is vague and arbitrary. This paper is aimed to study the effect of MIT on rainfall parameters. Hourly rainfall data were analysed for MIT values of 2hr, 4hr, 6hr, 9hr, 12hr, 18hr and 24hr. Results indicate that the rainfall frequency per annum is reduced from 199 to 89 when the MIT is altered from 2hr to 24hr. The mean depth, duration and inter-event time were increased with an increase in MIT while the mean intensity is decreased. Similarly, statistical parameters of maximum, standard deviation, CV, skewness and kurtosis were affected as the MIT value is altered. The results highlight the sensitivity of rainfall characteristics to MIT and as such care needs to be taken in the selection of MIT values in any study. © EuroJournals Publishing, Inc. 2010.